Pengaruh Perhatian Orang Tua, Disiplin dan Motivasi terhadap Hasil Belajar Ekonomi melalui Aktivitas Belajar Siswa - Mira Apriyani; Nurdin Nurdin; Tedi Rusman (Economic Education and Entrepreneurship Journal, 2020)
This research aimed to know about the influence of parent’s attention, discipline study, and learning motivation to the Student’s economic learning result through learning activities in IX Social Class of SMA Muhammadiyah 2 Bandar Lampung in academic year 2019/2020. The population in this study were eleven grade students social of SMA Muhammadiyah 2 Bandar Lampung with a total of 69 students. Using the T Yamane formula with simple random sampling obtained a sample of 58 students. The method used in this study is descriptive verification with ex post facto approaches and surveys. Data collection techniques used were observation, interviews, questionnaires and documentation. Hypothesis testing is done by T test and Ftest. The result of the analysis show that there is influance of parent’s attention, discipline study and learning motivation through learning activities towards integreted economic learning outcomes with a level of determination of 0,892 or 89,2%.